Identificación y Caracterización de las Especies Forestales Nativas, en tres Comunidades del cantón Echeandía, provincia Bolívar - Vargas Caballero, José Luis (2016)
The forests are essential to maintain an appropriate balance in the environment and in the biodiversity. The identification and characterization of the native forest species is a requirement in the planning, development and execution of the works dasonómicas. For this work he/she thought about as objectives: i) Identify the dominant native forest species in the Communities, Oronguillo, the Vaquera, and Chinivi. ii) Determine the morphological characteristics that present each one of the existent native species in the study areas. iii) Carry out a study dasonométrico of the native forest species. Progressively has left losing the native vegetable covering in lands of the diverse communities, caused by the application of an inadequate agriculture and for the firewood necessity like fuel, these stocks have led to a state of loss and extinction of the forest species; this pressure has made that the forest goes disappearing being some few relicts boscosos like samples of the old landscape. In the canton Echeandía is not current statistical registrations of the quantity of even existent native forest species. This investigation was carried out in the rodals of the communities of Oronguillo, The Vaquera and Chinivi, of the canton Echeandía, Bolívar of province. It was calculated the frequency, arithmetic mean, maximum value, minimum and Variance. The results were: the identified families are Fabaceae and Moraceae with 3 species, Polygonaceae registered 2 species. Bombacaeae; Staphyleaceae; Meliaceae; Cecropiaceae; Bignoniaceae; Euphorbiaceae; Clusiaceae; Malvaceae; Amaranthaceae; Rutaceae; Myristicaceae; Ulmaceae and Solanaceae 1 species. The identified and characterized species are: Raft; axe End; Rubber; Cedrillo; white Cedar; red Cedar; Fernán Sánchez; Guabo; Guarumo; Guaiac; Milkman; Mammee; Matapalo; Grinder; Moradilla; stupid Morals; Orange tree; Breast; hen Blood; dove Sapan and Tambora. In Oronguillo in dove Sapan registers the highest averages in the DAP with 87,54 cm; 37,50 m of it ties and 19,00; 0,60 m2 and 8,92 m3 of AB and VM. In the Vaquera the Guaiac reached the highest securities with 54,11 cm of DAP, 0,23 m2 of AB and 2,66 m3 of VM. The biggest AT and it was given in Fernán Sánchez with 45,00 and 20,75 m. In Chinivi the species Matapalo had the biggest DAP in 66,16 cm, it ties of 27,50 m; AB of 0,34 m2 and a MV of 2,29 m3. In Oronguillo the biggest DR registered in the stupid Morals with 24,14%. The biggest Gilds and ÍVI was given in the species dove Sapan with 36,44% and 30,55%. In The Vaquera the biggest DR one had in the species Grinder with 25,00%; the adult Gilds the Guaiac it was given with the 12,66. The biggest IVI was calculated in the species Grinder with 30,98%. In Chiniví the biggest DR was given in red Cedar with 21,62%; the one Gilds and bigger IVI registered in Matapalo with 18,36%; 31,88%.